Metformin and Lifestyle Modification in Polycystic Ovary Syndrome: Systematic Review: Effects of Lifestyle Modification on Polycystic Ovary Syndrome (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Polycystic ovarian syndrome (PCOS), a prevalent endocrine disease with reproductive and metabolic implications, causes anovulation, infertility, and a higher incidence of diabetes mellitus. Its aetiology is strongly linked to obesity, particularly central obesity, and insulin resistance. The primary treatment strategy is dietary weight loss however, effective methods for achieving and maintaining weight loss, as well as reproductive and metabolic improvements, are unknown. Lifestyle modification programs focused on behavioral management and nutritional and exercise treatments have decreased the incidence of diabetes and metabolic syndrome in the general population, and have shown some early effectiveness in improving reproductive outcomes in polycystic ovarian syndrome patients. However, since there is a scarcity of research on successful food and exercise programs for polycystic ovarian syndrome, organized recommendations for adopting components of lifestyle modification programs in this group should be assessed.